Preferred green amenities among home buyers [electronic resource] - Eliza, Ong Yuk Teng 1990-, author (2014)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2014